(untitled) (Baghdad Science Journal, 2025)
The D.C electrical and thermoelectrically properties of randomly mixed isolator – electrolyte system as (Al/ PVC – LiF/Al) junction consisting of polyvinyl chloride (PVC)resin reinforced with Lithium Fluoride (LiF) powder were studied. A comparison is made the properties of (PVC) material with varying percentage of (LiF) powder (0%, 30%, 50%, 80%)to find out the effect of reinforcement of isolator material. The composites dissolving in 10ml form tettraHaedroflourn (THF) and Solution were the castled in Petri dish and Laved it dry in the air, The out coming Sample were disc - Like shape of a diameter of about 3cm and thickness reneged between (0.01- 0.018) cm . The composites dissolving in 10ml form tettraHaedroflourn (THF) and Solution were the castled in Petri dish and Laved it dry in the air, The out coming Sample were disc - Like shape of a diameter of about 3cm and thickness reneged between (0.01- 0.018) cm . The experimental results show that current and the conductivity of (PVC - LiF) composites increase by three orders of magnitude when the volume fraction (LiF Vol.%) increase and so dose with temperature. The activation energy of the thermal rate - process of the electrical conductivity is determined and found to decrease with increasing the LiF vol. % content. We find that this composite has good conductivity, light weight and easily manufactured. These very good ideal characteristics can make the composite very suitable to be used commercially